Proses Berpikir Kreatif Siswa Tipe Sekuensial Abstrak dan Acak Abstrak pada Pemecahan Masalah Biologi - Herlina Herlina; Aprizal Lukman; Maison Maison (Universitas Jambi, 2016)
The aim of the research is to describe the creative thinking process of abstract sequential and abstract random type-students in solving biological problem. The research conducted on two subjects that had differences in the type of the thinking that is abstract sequential type-student (STBSA) and abstract random type-student (STBAA) at Attaufiq Senior High School Jambi city. The data were selected according to the purpose of research. The data was collected by interviewing and modified think aloud method. Data was analyzed by process of creative thinking frame work based on Polya’s problem solving steps. The over all results of the study concluded that the process of STBSA’s creative thinking conducted sequentially from the first stage to the last stage. The data which obtained according to problem-solving strategies and the steps in solving problems. The indicators of creativity are notified in the form of fluency, flexibility, originality, and the detail of biological solving problems. While STBAA, the steps of creative thinking process is done randomly and not sequentially. The results of the problem solving which conducted is not be conviced because STBAA used more insight, imagination and logic. Then, in terms of creativity, the flexibility of STBAA is not appropriate to the indicator to solve problems because only applying one method of complishment, doesn’t have capability to produce a variety of ideas to implement the problem solving and not able to present a concept in different ways during biological problems solving. STBSA precisely solves the problem exactly, because it believes in the results of the thinking, as well as maintaining the criticality in the process of biological solving problems. While STBAA is less precise in solving problems due to the less of the self-confidence, less critical and contented easily in the process of solving biological problems.